Patent Cooperation Treaty (PCT) : done at Washington on June 19, 1970, amended on September 28, 1979, modified on February 3, 1984, and on October 3, 2001 : and Regulations under the PCT (as in force from July 1, 2022). (World Intellectual Property Organization, 2022)
The Patent Cooperation Treaty makes it possible to seek patent protection for an invention simultaneously in each of a large number of countries by filing an "international" patent application. Such an application may be filed by anyone who is a national or a resident of a Contracting State.